Quantitative evaluation of the pulmonary microdistribution of TiO2 nanoparticles using X‐ray fluorescence microscopy after intratracheal administration with a microsprayer in rats. Issue 6 (23rd January 2015) - Zhang, Guihua; Shinohara, Naohide; Kano, Hirokazu; Senoh, Hideki; Suzuki, Masaaki; Sasaki, Takeshi; Fukushima, Shoji; Gamo, Masashi
Abstract: The unevenness of pulmonary nanoparticle (NP) distribution, which hinders the establishment of an absolute dose–response relationship, has been described as one of the limitations of intratracheal administration techniques for toxicological assessment of inhaled NPs. Quantification of the NP microdistribution would facilitate the establishment of a concentration–response relationship in localized regions of the lung; however, such quantitative methods have not been reported. Here, we established a quantitative method for evaluating pulmonary TiO2 NP microdistribution in rats using X‐ray fluorescence microscopy. Ti intensity in lung sections from rats intratracheally administered 10 mg kg –1 TiO2 NPs with a microsprayer was measured using X‐ray fluorescence with a 100 µm beam size. Ti reference samples were prepared by dropping different concentrations of Ti solutions on glass slide or lung sections of untreated rat. Ti intensity increased linearly with Ti content in the reference samples on both substrates. The detection limit of TiO2 was estimated to be 6.3 ng mm –2 . The reproducibility was confirmed for measurements done in the short‐ (2 weeks) and long‐term (6 months). The quantitative results of TiO2 NP microdistribution suggested that more TiO2 NPs were distributed in the right caudal and accessory lobes, which are located downstream of the administration direction of the NP suspension, and the lower portion of each lobe. The detection rates of TiO2 NPs were 16.6–25.0%, 5.19–15.6%, 28.6–39.2%, 21.4–38.7% and 10.6–23.2% for lung sections from the right cranial, middle, caudal, accessory and left lobes, respectively. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : The unevenness of pulmonary nanoparticle (NP) distribution, which hinders the establishment of an absolute dose‐response relationship, has been described as one of the limitations of intratracheal administration techniques for toxicological assessment of inhaled NPs. Quantification of the NP microdistribution would facilitate the establishment of a concentration‐response relationship in localized regions of the lung; however, such quantitative methods have not been reported. Here, we established a quantitative method for evaluating pulmonary TiO2 NP microdistribution in rats using X‐ray fluorescence microscopy.